PERAN SIKAP DALAM MEMEDIASI PENGARUH INNOVATIVENES, MATERIALISME DAN FINANCIAL PRESSURE TERHADAP NIAT BELI PRODUK PRE LOVE - Dewa, Muhammad Rakha Kusuma; Kuswati, Rini (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the influence of psychological and social factors on the purchase intention of secondhand clothing among Generation Z. Using a quantitative approach, data were collected from 203 Generation Z respondents who had purchased secondhand clothing through a structured questionnaire based on Likert scale. The sample was selected using purposive sampling to ensure respondents met specific criteria regarding secondhand product purchase experience. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via Smart PLS 3.2 to test the validity, reliability, and relationships between variables, both direct and mediated effects. The results indicate that factors such as fashion innovativeness, materialism, financial pressure, and attitudes toward trends and cleanliness significantly influence the purchase intention of secondhand clothing, mediated by attitudes toward trendy styles. These findings provide important insights into Generation Z consumer behavior and offer practical implications for secondhand clothing businesses in designing targeted marketing strategies